Hydrilla verticillata Density as a Bioindicator of Pollution in the Waters of Lake Talaga, Dampelas District - Azizatul Khasanah; Astija; Amalia Buntu; Aan Febriawan; Mursito S. Bialangi; Vita Indri Febriani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to determine the density of Hydrilla verticillata in Lake Talaga and to evaluate its potential as a bioindicator of changes in water quality caused by domestic pollution. The study was conducted at three stations, where physicochemical parameters were measured, including temperature, pH, light intensity, turbidity, dissolved oxygen, and the heavy metals Pb, Fe, and Cu. The results showed that water temperature ranged from 26 to 28°C and dissolved oxygen from 8.04 to 8.49 mg/L, indicating conditions that still support aquatic life. Heavy metal concentrations were below the established water quality standards. However, the pH was categorized as highly alkaline, and the highest turbidity was recorded at the station located near residential areas, suggesting environmental pressure associated with domestic activities. The density of Hydrilla verticillata varied among stations, reaching 607,333.3 ind/ha at Station II (high category), 180,000 ind/ha at Station I (moderate category), and 6,066 ind/ha at Station III (low category). The high density observed in the residential area indicates nutrient enrichment that may stimulate excessive growth of aquatic vegetation. This condition suggests symptoms of eutrophication and indicates that Lake Talaga is experiencing localized light to moderate pollution. Therefore, the density of Hydrilla verticillata has strong potential to be used as a bioindicator for assessing changes in water quality.